Aux sources de l’Éden éducatif nordique. Images véhiculées en France de l’instruction primaire finlandaise au cours de la deuxième moitié du XIXe siècle (1851-1911) - Johann-Günther Egginger (Recherches en Éducation)
With the wonderful prestige of its international PISA test scores, the Finnish education system is the subject of many French studies that seek to determine the secrets of such success, and tend to idealize this Finnish "miracle". This paper proposes the hypothesis of a mystification of the Finnish system, which dates back to the earlier period of universal expositions of the late 19th century. The data consist of printed materials related to exhibitions and school collections. The analysis shows an already “successful” education system, from the late 19th, with respect to the excellent reading command by the vast majority of the Finnish people.